Analisis Institusionalisasi Partai Politik Pada Pemilu Legislatif Tahun 2014 - Firmadi, Sidik; Purwaningsih, Titin (Universitas Muhammadiyah Yogyakarta, 2016)
The institutionalization of a political party is one of the factors that affect the stability of the votes or the number ofseats of a political party in the election.In the 2014 legislative election, the votes or the number of seats of theDemocrat Party of the Province of Lampung decreased compared to the 2009 legislative election. However, the vote orthe number of seats in the 2014 legislative election is still fairly stable when compared with the vote or the number ofseats of the Democrat Party in other regions.The stability of the votes or the number of seats of the Democrat Party ofthe Province of Lampung in the 2014 legislative election is interesting to study to investigate whether the stability isinfluenced by the factor of the institutionalization of the party or be influenced by other factors such as patronage andclientelism.This research uses descriptive method with qualitative approach. In this study, the researchers alsoconducted an analysis of the index of institutionalization of political party to determine the level of institutionalization ofthe Democrat Party of the Province of Lampung.This study takes the research sites in the Province of Lampung with theDemocrat Party as the research object. This study concludes that: First, the level of institutionalization of the DemocratParty of the Province Lampung is in the medium category.Second, the stability of the votes of the Democrat Party of theProvince of Lampung is not solely influenced by the institutionalization of the party, but is influenced by two otherfactors which are more dominant, namely the practice of patronage and clientelism in governor election and legislativeelection which are carried out simultaneously and the practice of patronage and clientelism performed by the DemocratParty candidates. The recommendation of this study is that the Democrat Party of the Province of Lampung mustimmediately resolve the flaws in the institutionalization dimension, especially in the number of the power of members orcadres, the number of the networking of mass organization or organizational wing of the party, so that in the future, thepotential of the power of the members or cadres and mass organizations or organizational wing of the party can runmaximally so the party machinery can operate more effectively during the elections.